Pengaruh Nilai Pelanggan Dan Variasi Produk Terhadap Kepuasan Pelanggan Soehendar Coffee - Muhamad Fadilah; Irma Mardian (FEB Universitas Maritim Semarang, 2023)
This research aims to determine the influence of customer value and product variety on Soehendar Coffee customer satisfaction. Data collection techniques use observation, questionnaires and literature study. The sample in this study was 30 respondents with the sampling technique being purposive sampling, namely customers who had purchased Soehendar Coffee products at least once. The data analysis technique uses multiple linear regression analysis. The research results show that partially, neither customer value nor product variety have a significant influence on Soehendar Coffee customer satisfaction. Simultaneously, customer value and product variety have a significant influence on Soehendar Coffee customer satisfaction.